Medical documentation practice and associated factors among health workers at private hospitals in the Amhara region, Ethiopia 2021 - Mulugeta Desalegn Kasaye; Miftah Abdella Beshir; Berhanu Fikadie Endehabtu; Binyam Tilahun; Habtamu Alganeh Guadie; Shekur Mohammed Awol; Mulugeta Hayelom Kalayou; Tesfahun Melese Yilma (BMC, 2022)
Abstract Introduction Medical documentation is an important part of the medical process as it is an essential way of communication within the health care system. However, medical documentation practice in the private sector is not well studied in Ethiopian context. The aim of this study was to assess the practice of medical documentation and its associated factors among health workers at private hospitals in the Amhara region, Ethiopia. Method An institution-based cross-sectional quantitative study supplemented with a qualitative design was conducted among 419 health workers at the private hospitals in the Amhara Region, Ethiopia from March 29 to April 29 /2021. Data were collected using both a self-administered questionnaire and interview guide for quantitative and qualitative respectively. Data were entered using Epi data version 3.1 and analyzed using SPSS version 20. Descriptive statistics, Bi-variable, and multivariable logistic regression analysis were performed. In-depth interviews were conducted using semi-structured questionnaires with eight respondents to explore the challenges related to the practice of medical documentation. Respondent's response were analyzed using OpenCode version 4.03 thematically. Results Four hundred seven study participants returned the questionnaire. Nearly 50 % (47.2%) health workers had of good medical documentation practice. Health workers who received in-service training on medical documentation AOR = 2.77(95% CI: [1.49,5.14]), good knowledge AOR = 2.28 (95% CI: [1.34,3.89]), favorable attitude AOR = 1.78 (95%CI: [1.06,2.97]), strong motivation AOR = 3.49 (95% CI: [2.10,5.80]), available guide line formats AOR = 3.12 (95% CI: [1.41,6.84]), eHealth literacy AOR = 1.73(95% CI: [1.02,2.96]), younger age AOR = 2.64 (95% CI:[1.27,5.46]) were statistically associated with medical documentation. Conclusion More than half of the medical services provided were not registered. Therefore, it is important to put extra efforts to improve documentation practice by providing planed trainings on standards of documentation to all health workers, creating positive attitudes and enhancing their knowledge by motivating them to develop a culture of information.